THE EFFECTIVENESS OF ENGLISH READING MATERIAL BASED ON ISLAMIC VALUE FOR ISLAMIC HIGHER EDUCATION - Andi Mukarramah Nagauleng; Nur Halimah; Muhammad Imran (Schemata: Jurnal Pascasarjana UIN Mataram, 2019)
Reading skill as a part of receptive skills are given the first priority in language curriculum and in Islamic education. Reading skill is important because it is a medium of communication and a tool for learning. This study aims to find out the effectiveness of English reading material based on islamic value for Islamic higher education in IAIN of Manado, that support the students learning and coprehension the Islamic values through the English reading materials. This study applied a qualitative approach using a case study design where researcher conducted the in-depth exploration of the events, processes, and activities to one or more people who are bound by time and activity. The researcher used this type of research is due to the subject of this study is only one class of second semesters students, they are 21 students. The researcher was a key instrument who participated actively in the activities. In collecting data, the researcher used observation, interview, field note, and documentation. The data were analyzed concurrently with the data collection interactively through the process of data reduction, display and verification using domain analysis, taxonomic, conventional, and cultural theme analysis. The researcher found that with apply Islamic value in reading texts materials, beside students more easily understand it, texts Islamic value can also improve the character of students as Muslim students.